An introduction to computer-aided amplifier circuit analysis and design - Sta. Maria, Teodoro C. (1969)
The main objective of this thesis is to introduce on the local scene some of the concepts and techniques of computer-aided amplifier circuit analysis and design. One network analysis programs called the Calahan Network Analysis Program was obtained from abroad and was adapted to the UP's IBM 360 Model 40 Digital Computer. Some modifications were made on the main program and a set of instructions for the preparation of input data cards were written. Some computer-aided analysis techniques are presented and illustrated by means of examples. A computer-aided design of a wideband transistor amplifer is also discussed and illustrated. From the computer resulsts of the illustrative examples given and for the particular network analysis programs used in this work, certain conclusions, concerning the benefits derived from the use of the program, are reached.
Thesis (M. S. Electrical Engineering)--University of the Philippines, Diliman.
Keywords: Amplifiers (Electronics) -- Computer-aided design